On the ε-sufficient control in one merton problem with “physical” white noise - Bondarev, B. V.; Kozyr', S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider the Merton problem of finding the strategies of investment and consumption in the case where the evolution of risk assets is described by the exponential model and the role of the main process is played by the integral of a certain stationary “physical” white noise generated by the centered Poisson process. It is shown that the optimal controls computed for the limiting case are ε-sufficient controls for the original system.